2012
DOI: 10.1371/journal.pone.0037333
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Analysis of Angiogenic Growth in Three-Dimensional Microfluidic Cell Cultures

Abstract: We demonstrate ensemble three-dimensional cell cultures and quantitative analysis of angiogenic growth from uniform endothelial monolayers. Our approach combines two key elements: a micro-fluidic assay that enables parallelized angiogenic growth instances subject to common extracellular conditions, and an automated image acquisition and processing scheme enabling high-throughput, unbiased quantification of angiogenic growth. Because of the increased throughput of the assay in comparison to existing three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 51 publications
4
119
0
Order By: Relevance
“…mammary adenocarcinoma cells embedded in a collagen type I hydrogel (Fig. 1A) (17,20). By holding one medium channel (upstream) at a higher fluid pressure than the other channel (downstream), a stable and repeatable flow field can be generated through the collagen gel (Movie S1 and SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…mammary adenocarcinoma cells embedded in a collagen type I hydrogel (Fig. 1A) (17,20). By holding one medium channel (upstream) at a higher fluid pressure than the other channel (downstream), a stable and repeatable flow field can be generated through the collagen gel (Movie S1 and SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…Spheroids of 40-to 70-μm diameter were selected with sieves as reported (66). Spheroids were seeded in the central region of a microfluidic device using standard soft lithography techniques (94,95). The central region of the device is flanked by two channels.…”
Section: Fgfr4-fiin-2 and Fgfr4 V550l-fiin-3 Crystallization And Strumentioning
confidence: 99%
“…In our microfluidic device (Farahat et al, 2012), shown in Figure 1, we inject collagen gel between the two channels. Through one channel,we seed cells, which attach to one side of the collagen and form a monolayer.…”
Section: Cell-matrix Interactions and 2d/3d Imagesmentioning
confidence: 99%
“…A confocal microscope captures fluorescence and transmitted light images of each migration region, including the cell monolayer. Image adapted from (Farahat et al, 2012)). …”
Section: Introductionmentioning
confidence: 99%